Ultrasonographic Assessment of Knee in Patients with Rheumatoid Arthritis: Is it an Effective Imaging Method for Initial Evaluation? - Cüneyt YÜCESOY,; Gülden GENÇ,; Ajda BAL,; Bahri KEYİK,; Emine ÖZTÜRK,; Meriç TÜZÜN,; Aytül ÇAKÇI,; Baki HEKİMOĞLU1, (Archives of Rheumatology, 2011)
Objectives: This study aims to evaluate the effectiveness of ultrasound (US) as an initial imaging method in patients with rheumatoid arthritis. Patients and methods: Thirty consecutive (25 females, 5 males; mean age 55.9 years; range 38 to 74 years) rheumatoid arthritis patients with 30 symptomatic knees were included in the study between November 2006 and August 2008. The intrarticular effusion, synovial proliferation, popliteal cysts and patellarquadriceps tendonitis and weight bearing femoral condylar cartilage thickness and morphology were assessed by US and, within five days, a magnetic resonance imaging (MRI) examination was performed. The results of both examinations were interpreted blindly and compared by two experienced radiologists in their field. Results: In the comparisons of the results of US and MRI examinations, both modalities were mostly concordant. A significant rate of concordance was found between US and MRI results, for joint effusion (k=0.683, p<0.001) synovial proliferation (k=0.595, p<0.001), popliteal cysts (k=0.865, p<0.001) and tendonitis (k=0.889, p<0.001). On the US, the mean medial and lateral femoral condylar cartilage thickness was calculated as 2.1 mm on both sides, whereas the MRI revealed 1.8 mm on the medial and 1.9 mm on the lateral part. In the statistical analysis, the condylar cartilage was significantly thicker on the US than on the MRI (p<0.001). On the other hand, there was a significant correlation between two modalities regarding the cartilage morphology, both on the medial (k=0.658, p<0.001) and the lateral part (k=0.851, p<0.001). Conclusion: The high correlation rate between the results of US and MRI have shown that in rheumatoid arthritis patients with knee joint involvement, US is an easily accessible and effective alternative method of examination.